2014
DOI: 10.5120/18151-9413
|View full text |Cite
|
Sign up to set email alerts
|

Image Classification using Tag and Segmentation based Retrieval

Abstract: In today's scenario when social media sites are widely used and high resolution images are shared. Tagging is an important approach for the retrieval of images in various applications. These are also used to manage personal media data. There are various techniques implemented for the image retrieval such as feature based, histogram based and transformation based but these techniques are not efficient in terms of classification ratio and accuracy. Here in this paper various tag based image technique are discuss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Maximize performance and efficiency material, such as pornography, but also because videos are widely spread through social media, inhibiting the application of controlled priori data [33][34][35].…”
Section: Categories and Applications Of Big Data Analyticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Maximize performance and efficiency material, such as pornography, but also because videos are widely spread through social media, inhibiting the application of controlled priori data [33][34][35].…”
Section: Categories and Applications Of Big Data Analyticsmentioning
confidence: 99%
“…Thus, each instance can occur at most once in the sampled data. If the complete dataset has n instances and we need k samples, then it can be shown that with the reservoir sampling algorithm [35], each item in the full dataset has the same probability (i.e., k/n) of being chosen for the sampled dataset. We initially select the first k instances of the dataset for our sample.…”
Section: Samplingmentioning
confidence: 99%
“…The research works in [33] and [34] offer functions to visual attributes to make multimedia accessible. Content retrieval applications are explored in [35][36][37][38][39][40][41][42]. Feature analysis and reduction based on several related areas are also explored in [19,20,[41][42][43][44][45][46][47][48].…”
Section: Related Workmentioning
confidence: 99%
“…[31,32] use visual functions to access multimedia and filtering. Articles [33][34][35][36] are based on content retrieval.…”
Section: Related Workmentioning
confidence: 99%